ASSESSMENT OF FISH POPULATION DYNAMICS IN LAKE ZAISAN USING A COHORT APPROACH BASED ON RESEARCH AND COMMERCIAL CATCH DATA - Shapen, K.; Gabbassov М.; Rakhymova А.; Kasymkhanov , A. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
This paper proposes a new approach for estimating changes in the abundance and biomass of fish populations in water reservoirs based on sample data from research and commercial fishing. The developed approach takes into account the age structure and dynamics of changes by cohort, without requiring additional information on absolute fish abundance. To reduce the influence of fluctuations and uncontrolled factors, pre-processing of the data using third-degree polynomial regression is used. A mechanism for conditionally accounting for sex composition in biomass calculations is also implemented, allowing for increased estimation accuracy. The presented formulas provide a flexible and adaptive analysis method suitable for conditions with limited or incomplete data. The new assessment approach provides reproducible and comparable results, enabling monitoring of population status and tracking trends in the abundance and biomass of fish resources. The proposed mathematical model is an alternative cohort method for estimating fish populations and their biomass, which should be considered in conjunction with other approaches to stock assessment and applied jointly to management decision-making in fisheries.